Gene–gene interactions in IL23/Th17 pathway contribute to psoriasis susceptibility in Chinese Han population. (22nd August 2012) - Wang, W.‐J.; Yin, X.‐Y.; Zuo, X.‐B.; Cheng, H.; Du, W.‐D.; Zhang, F.‐Y.; Yang, S.; Zhang, X.‐J.
Abstract: Background Psoriasis is a common chronic inflammatory skin disease. IL23/Th17 is a newly confirmed pathway in psoriasis. Objective To investigate the gene–gene interactions in IL23/Th17 pathway underlying psoriasis. Methods A total of 299 single‐nucleotide polymorphisms from 11 genes in IL23/Th17 pathway were genotyped on 1139 patients with psoriasis and 1694 controls. Multifactor dimensionality reduction and logistic regression algorithms were applied to explore the gene–gene interactions. Results We found that there were a three‐way interaction among IL21, CCR4 and TNF(χ 2 = 5.02(1), P = 0.025) and three pair‐wise gene–gene interactions between IL12RB1 and CCR4(χ 2 = 11.66(4), P = 0.0201), IL22 and CCR4 (χ 2 = 11.97(4), P = 0.0176), IL12RB1 and IL6 (χ 2 = 7.31(1), P = 0.0069) in psoriasis. Conclusions Our results might be helpful for explaining the missing heritability of the psoriasis due to epistasis and provide a deep insight into the important role of the IL23/Th17 pathway in the pathogenesis of psoriasis.